Elderly health promotion and health prevention practices against mistreatment: an integrative review - Mariana Ramos Guimarães; Donizete Vago Daher; Florence Tocantins Romijn; Aline Ramos Velasco; Ândrea Cardoso de Souza (Universidad de Alicante, 2018)
Objective: Analyze scientific literature how the healthcare profession practices contemplate the promotion of health and prevention of elder abuse. Method: It is an integrative review, whose question is, "How the health practices developed by health professionals include elderly health promotion and health prevention of mistreatment?" The search was done on the MEDLINE and LILACS, using the descriptors: "Health of the Elderly" and "Elder Abuse". Were included originals articles published in Portuguese, English and Spanish languages, between 1994 to 2015. Duplicated articles, dissertations on the databases, editorials, reviews, book reviews / chapters, and articles with paid access were excluded. Results: The sample was composed by nine articles that analyzed through content analysis process. It was built up categories: Elderly health promotion practices and Prevention practices of elder abuse. Conclusion: Gaps in knowledge were identified. Were evasive the actions of violence surveillance. Actions of permanent education about health promotion and health prevention against of elder abuse still need to be instituted.